IDEF modeling of PCB assembly process - Xu, Kun. (2008)
The objective of this dissertation is to produce a detailed description of a PCB assembly process for a local semiconductor company from five different views, namely, function view, information view, process view, resource view and organization view, using the IDEF* methodology.